2020
DOI: 10.1093/jcbiol/ruaa004
|View full text |Cite
|
Sign up to set email alerts
|

The crustacean Armadillidium vulgare (Latreille, 1804) (Isopoda: Oniscoidea), a new promising model for the study of cellular senescence

Abstract: Senescence, the decline of physiological parameters with increasing age, is a quasi-ubiquitous phenomenon in the living world. The observed patterns of senescence, however, can markedly differ across species and populations, between sexes, and even among individuals. To identify the drivers of this variation in senescence, experimental approaches are essential and involve the development of tools and new study models. Current knowledge of the senescence process is mostly based on studies on vertebrates and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Survival abilities to the second infection decline in old w − females compared to young ones of same priming treatment, but this decline was not observed for w − males: old males survived as well as young males comparing the same priming treatment. In A. vulgare , we know that genders display same changes in phenoloxidase activity and haemocyte concentrations with ageing and are therefore both affected by cellular senescence (Depeux et al., 2020; Sicard et al., 2010). However, Depeux et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival abilities to the second infection decline in old w − females compared to young ones of same priming treatment, but this decline was not observed for w − males: old males survived as well as young males comparing the same priming treatment. In A. vulgare , we know that genders display same changes in phenoloxidase activity and haemocyte concentrations with ageing and are therefore both affected by cellular senescence (Depeux et al., 2020; Sicard et al., 2010). However, Depeux et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, Depeux et al. (2020) showed that females have higher β‐galactosidase activity and lower immune cell viability than males, suggesting that females are physiologically more senescent than males of the same age. The “accelerated” senescence of females could be the consequence of a reproductive evolutionary cost, females allocating more physiological resources in reproduction through ageing than males (Bonduriansky et al., 2008; Lawniczak et al., 2007; Sheldon & Verhulst, 1996; Thiel, 2003; Vinogradov, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the groups CT, HT, CM, and LM) for measuring the level of our set of physiological traits (i.e. immune cells parameters and β-galactosidase activity) developed in Depeux et al (2020a).…”
Section: Physiological Traitsmentioning
confidence: 99%
“…For survival data, the effect size was the hazard ratio, calculated as the exponential of the regression parameter (Collett 2003). When the selected model did not include the effect of the stress, we took the model with the variable stress as fixed factor to obtain a size effect as made in Depeux et al 2020a. All statistical analyses and representations of results were performed using the software R 4.2.1 (R core Team 2022).…”
Section: Statistical Analysesmentioning
confidence: 99%